2017
DOI: 10.1007/s11065-017-9350-8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Interventions for Cognitively Healthy, Mildly Impaired, and Mixed Samples of Older Adults: A Systematic Review and Meta-Analysis of Randomized-Controlled Trials

Abstract: Cognitive interventions may improve cognition, delay age-related cognitive declines, and improve quality of life for older adults. The current meta-analysis was conducted to update and expand previous work on the efficacy of cognitive interventions for older adults and to examine the impact of key demographic and methodological variables. EBSCOhost and Embase online databases and reference lists were searched to identify relevant randomized-controlled trials (RCTs) of cognitive interventions for cognitively he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
103
2
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 190 publications
14
103
2
6
Order By: Relevance
“…Previous studies have noted that process-based training yields superior results compared with the other two types and also have resulted in promising transfer of training in participants up to very old age (Brehmer, Westerberg, & B€ ackman, 2012;Karbach & Verhaeghen, 2014;Zinke et al, 2014). According to the Oxford Centre for Evidenced-Based Medicine's criteria, the quality of evidence for previous clinical trials of executive function-related training was range from grade 1A to grade 1B (Chapman et al, 2013;Chiu et al, 2017;Mewborn, Lindbergh, & Miller, 2017;OCEBM Levels of Evidence Working Group, 2011). Therefore, the executive function-related training may be effective to improve older adults' cognitive-related functions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have noted that process-based training yields superior results compared with the other two types and also have resulted in promising transfer of training in participants up to very old age (Brehmer, Westerberg, & B€ ackman, 2012;Karbach & Verhaeghen, 2014;Zinke et al, 2014). According to the Oxford Centre for Evidenced-Based Medicine's criteria, the quality of evidence for previous clinical trials of executive function-related training was range from grade 1A to grade 1B (Chapman et al, 2013;Chiu et al, 2017;Mewborn, Lindbergh, & Miller, 2017;OCEBM Levels of Evidence Working Group, 2011). Therefore, the executive function-related training may be effective to improve older adults' cognitive-related functions.…”
Section: Introductionmentioning
confidence: 99%
“…Five reviews were classified as a mixed population, three included individuals with MCI and dementia (Hoefler, 2016;Kurz, Leucht, & Lautenschlager, 2011;Yang et al, 2018), one stated that they looked at participants without dementia (Floyd & Scogin, 1997) and one did not specify cognitive status (Pinquart & Sörensen, 2001). Four reviews synthesized pooled effects for more than one population: two reviews reported metaanalytical results for healthy older adults and MCI (Martin, Clare, Altgassen, Cameron, & Zehnder, 2011;Mewborn, Lindbergh, & Stephen Miller, 2017), one reported results for healthy older adults and dementia (Karr, Areshenkoff, Rast, & Garcia-Barrera, 2014), and one focused on individuals with MCI and dementia (Hill et al, 2017).…”
Section: About Here]mentioning
confidence: 99%
“…The mean effect estimate was 0.32 (0.05 to 0.59). Evidence from the two most comprehensive reviews with 'moderate confidence' ratings showed a small and significant effect in favour of CT on overall cognitive functioning; Lampit et al (2014) synthesized the results of 51 trials of computerized CT and reported an effect size of Hedge's g 0.22 (0.15 to 0.29) and Mewborn et al (2017) pooled the results of 48 trials with an overall effect size of Hedge's g 0.31 (0.24 to 0.39). In all, 15 of 19 reviews showed a significant intervention effect on objective cognitive outcomes ( Fig.…”
Section: Cognitive Outcomesmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] For example, using data from 97 randomized controlled trials (RCTs) examining a variety of cognitive training interventions in cognitively healthy adults and those with mild cognitive impairment (MCI) aged 60 and older, a Hedges' g of 0.30 (p<.001) that neither age, education, nor cognitive status significantly moderated was reported. 15 Using data from 17 RCTs in older adults with MCI, a Hedges' g of 0.35 (p<.001) was reported. 16 Focusing solely on speed-ofprocessing training (SOPT), a review of 17 RCTs 17 reported a Cohen's d of 0.71 (p<.001) on the targeted proximal outcome (useful field of view (UFOV)), 18,19 as well as transfer to real-world tasks including Cohen's d s of 0.27 (p<.001) on IADLs, 0.36 (p5.04) on driving mobility, and 0.21 (p5.04) on well-being.…”
mentioning
confidence: 99%